Flipped Classroom Learning Design Using the ASSURE Model - Sugiri, Wiku Aji; Priatmoko, Sigit; Basori, Basori (Universitas Sebelas Maret, 2020)
Limited learning time in class is one of the factors inhibiting instructional objectives. In connection with this problem, the flipped classroom is considered one form of the right strategy to achieve learning objectives. This research describes the development of a learning system based on the flipped classroom. The study was conducted at SMAN 10 Malang. The research subjects were 30 students in grade X. This development’s final product is the syntax of flipped classroom learning in PJOK subjects integrated with the ASSURE model. The development of this learning design has collaborated with the Unit Kegiatan Belajar Mandiri (UKBM)/ an independent learning design unit based on a learning management system (LMS). The validation results’ percentage of the learning design obtained a score of 93.33; the media validation results were 94.28; and, the content validation results were 92.00. The field trials’ results on the products also revealed satisfactory results with a percentage score of 80.61. Furthermore, the research subjects’ learning evaluation results interpreted that all students (100%) could achieve the KKM (Kriteria Ketuntasan Minimum) / minimum completeness criteria value. Thus, it can be concluded that the development of flipped classroom-based learning design is very effective or feasible to be implemented in PJOK.